Formal Modulation for Acoustic Performances of a Bridge - Tiazzoldi, Caterina; Tixier, Nicolas (ARCC Conference Repository, 2019)
In the last fifteen years in architecture the frequent use of design instruments such as algorithms, dynamical relations, parametric systems, mapping, morphogenesis, cellular automata and bifurcation with broken symmetry shows clearly how contemporary thinking in mathematics and physical sciences, dealing with complex dynamics, non-linear systems, chaos, emergent properties, resilience, etc., has changed the way we think about design and the life of today’s cities.